NMC453 : Creative digital photography / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2025)
This course introduces students to the operation of the digital single lens reflex (DSLR) camera and image enhancement using photo and video editing software. Students will learn the basic use of DSLR camera to produce still images and progressively create creative images using a variety of techniques. Topics include learning the DSLR camera features and related equipment, understanding light, movement and motion techniques, creative contents, and image enhancement using digital software. Students will also learn to explore other image techniques of high dynamic range photography, time lapse, hyperlapse, stop motion and experimental digital photography. This course will eventually prepare students with the basic and creative knowledge of producing still images, images in motion, and experimental images using DSLR camera.